Arquitetura residencial eclética em Belém do Pará (1870-1912): Um estudo da gramática das fachadas - FARIA, Maria Beatriz Maneschy (Universidade Federal do Pará, 2017)
In this research we studied the compositional grammar from the facade of the eclectic residential architecture of Belem, on the formal aspects of its elements, through relations of symmetry, rhythm, proportions, layout, dimensions and use of colors in each of its parts. The study is restricted to the type of residential basement and a deck in specimens without definite authorship. The research also considers the importance of facades in construction of collective identity, based on a sense of belonging in the community. Therefore, using the ethnographic method in the apprehension of memory, since the interventions historic preservation often disregards the need to address the conflict between the old (original stylistic features of the building) and the new (current needs or preferences ), an old dilemma between permanence and change. To conduct the analysis, we created three categories of facades: pure classicist facades, classical facades with eclectic elements and eclectic facades. By considering the facade classicist pure source eclectic facade, it was preferred to the polychromatic geometric and analyzes a) Comparative analysis over time of iconographic images of the search, b) compositional analysis of the relationships proportions, dimensions and arrangements of façade elements based on proportionality golden c) Visual observation of chromatic patterns found from prospecting pictorial. From this study it was possible to say that the pure classicist facades have a limited vocabulary in the composition of its grammar, with well defined rules, but the projects in its origin, do not obey the compositional principles learned, which leads us to conclude that based on imitation of other works, possibly without relying on the guidance of professional architecture. As the ratio of chromatic ranges between the various elements of the composition of their facades, we identify the existence of a principle chromatic. We believe that the model is not found chromatic complex and not contrasts, but nuances of tone, used with meanings. This study contributes to the understanding of the eclectic civil architecture of Belem.